The User Perspective in Lexicography: The Lemmatisation of Fixed Expressions in Duramazwi Guru reChiShona - Mpofu, Nomalanga (Lexikos, 2007)
Abstract: The article discusses the user perspective and information retrieval in relation to the lemmatisation of specific multi-word lexical units, namely fixed expressions, in the Shona monolingual dictionary, Duramazwi Guru reChiShona. It shows that the decisions arrived at in lemmatising fixed expressions were influenced by a user-driven approach. The article gives a comparative analysis of how fixed expressions were treated in previous Shona dictionaries and how they were subsequently dealt with in Duramazwi Guru reChiShona. Previous dictionaries have grappled with the problem of giving fixed expressions as run-on entries. Against the background of the user perspective, it will be argued that the lemmatisation of fixed expressions in monolingual dictionaries has certain advantages over previously used strategies.Keywords: FIXED EXPRESSION, HEADWORD, IDIOM, INTENDED USER, LEMMA, LEMMATISATION, MACROSTRUCTURE, MICROSTRUCTURE, MULTI-WORD LEXICAL UNIT, PITHY SAYING, PROVERB, RUN-ON ENTRY, USER, USER-FRIENDLY, USER PERSPECTIVEOpsomming: Die gebruikersperspektief in die leksikografie: Die lemma-tisering van vaste uitdrukkings in Duramazwi Guru reChiShona. Die artikel bespreek die gebruikersperspektief en inligtingsherwinning met betrekking tot die lemmatisering van spesifieke meerwoordige leksikale eenhede, naamlik vaste uitdrukkings, in die Sjona- eentalige woordeboek Duramazwi Guru reChiShona. Dit toon dat die besluite waartoe gekom is by die lem-matisering van vaste uitdrukkings beÃ¯nvloed is deur 'n gebruikersgedrewe benadering. Die artikel gee 'n vergelykende ontleding van hoe vaste uitdrukkings in vorige Sjonawoordeboeke bewerk is en hoe hulle vervolgens in Duramazwi Guru reChiShona behandel is. Vorige woordeboeke het met die probleem geworstel om vaste uitdrukkings as deurloopinskrywings te gee. Teen die agtergrond van die gebruikersperspektief word aangevoer dat die lemmatisering van vaste uitdrukkings in eentalige woordeboeke sekere voordele het bo vroeër gebruikte stategieë.Sleutelwoorde: VASTE UITDRUKKING, BEDOELDE GEBRUIKER, DEURLOOPINSKRY-WING, GEBRUIKER, GEBRUIKERSPERSPEKTIEF, GEBRUIKERSVRIENDELIK, IDIOOM, LEMMA, LEMMATISERING, MAKROSTRUKTUUR, MEERWOORDIGE LEKSIKALE EENHEID, MIKRO-STRUKTUUR, PITTIGE GESEGDE, SPREEKWOORD, TREFWOORD